Will and Its Importance in Value Internalization - Aramavičiūtė, Vanda (Acta Paedagogica Vilnensia, 2001)
In this article will is understood as a mechanism of value internalization. Altogether the focus of the article is on the essence of the will and ifs main functions. Also some peculiarities of the development of will are discussed, as well as the importance of good will in the internalization of spiritual values. As the highest form of the phenomena of the will, good will integrate withii1 itself and give meaning to other peculiarities of the will: fortitude, steadiness, intensity, quickness of wit, etc. The article also reveals some peculiarities of the will of older school students and it’s relation with some traits of students’ behaviour. Data of scientific research revealed, that also among the older school students there is evidence of the lack of intense efforts of will in consolidation of spiritual goodness in personal activities. It could be concluded, that in the older school age the problem of good will still remain urgent.